In vivo monitoring of urea cycle activity with 13C-acetate as a tracer of ureagenesis - Opladen, Thomas; Lindner, Martin; Das, Anibh M.; Marquardt, Thorsten; Khan, Aneal; Emre, Sukru H.; Burton, Barbara K.; Barshop, Bruce A.; Böhm, Thea; Meyburg, Jochen; Zangerl, Kathrin; Mayorandan, Sebene; et al. (Molecular genetics and metabolism, 2016)
Background - The hepatic urea cycle is the main metabolic pathway for detoxification of ammonia. Inborn errors of urea cycle function present with severe hyperammonemia and a high case fatality rate. Long-term prognosis depends on the residual activity of the defective enzyme. A reliable method to estimate urea cycle activity in-vivo does not exist yet. The aim of this study was to evaluate a practical method to quantify 13C-urea production as a marker for urea cycle function in healthy subjects, patients with confirmed urea cycle defect (UCD) and asymptomatic carriers of UCD mutations. - Methods - 13C-labeled sodium acetate was applied orally in a single dose to 47 subjects (10 healthy subjects, 28 symptomatic patients, 9 asymptomatic carriers). - Results - The oral 13C-ureagenesis assay is a safe method. While healthy subjects and asymptomatic carriers did not differ with regards to kinetic variables for urea cycle flux, symptomatic patients had lower 13C-plasma urea levels. Although the 13C-ureagenesis assay revealed no significant differences between individual urea cycle enzyme defects, it reflected the heterogeneity between different clinical subgroups, including male neonatal onset ornithine carbamoyltransferase deficiency. Applying the 13C-urea area under the curve can differentiate between severe from more mildly affected neonates. Late onset patients differ significantly from neonates, carriers and healthy subjects. - Conclusion - This study evaluated the oral 13C-ureagenesis assay as a sensitive in-vivo measure for ureagenesis capacity. The assay has the potential to become a reliable tool to differentiate UCD patient subgroups, follow changes in ureagenesis capacity and could be helpful in monitoring novel therapies of UCD.